Circadian signatures of adipose tissue in diet-induced obesity - Xin, Haoran; Zhang, Jianxin; Huang, Rongfeng; Li, Lihua; Lam, Sin Man; Shui, Guanghou; Deng, Fang; Zhang, Zhihui; Li, Min-Dian (Frontiers in Physiology, 2022)
High-fat diet (HFD) feeding rewires circadian rhythms of peripheral organs including the liver and adipose tissue. While the liver has been extensively studied, it remains largely unknown whether and how HFD organizes circadian biology in adipose tissue. Here, we took a systems approach to profile diurnal transcriptome of adipose tissue in diet-induced obese mice either put on low-fat diet (LFD) that reduces weight or still fed HFD. We detected about 200 and 2,500 diurnal genes in HFD and LFD, respectively. Pathway analysis revealed that rhythmic pathways in HFD are represented by circadian rhythm, ribosome biogenesis, nucleosome organization, whereas those in LFD are represented by myeloid cell function. Remarkably, the majority of the circadian clock genes except Clock exhibit robust diurnal rhythm in the adipose tissue of HFD-fed mice. Analysis of mRNAs and proteins in another cohort of HFD-fed mice confirmed that Clock lost rhythmicity at the transcript level but not in proteins. Diet reversal to LFD specifically restores diurnal difference in Clock transcripts in adipose tissue. We matched transcriptomics data with global profiling of neutral lipids, and found that lipid metabolism catalyzed by triglycerol hydrolase Ces1d is a key circadian feature that is activated by diet reversal. Together, our work defines the circadian signatures in the adipose tissue of diet-induced obese mice, and their flexibility upon dietary intervention, and shed light on potential clock-modulated tissue-specific pathways during obesity.